Capillary Refill Time Monitoring System using Optical Fibre Sensor - Rosli, Nurdania Irisha; Wan Zaki, Wan Suhaimizan (Evolution in Electrical and Electronic Engineering, 2023)
Capillary Refill Time (CRT) assessment in healthcare plays a crucial role in evaluating perfusion and guiding treatment decisions. However, manual observation and subjective estimation of CRT using traditional counting methods are prone to human errors. Additionally, the lack of standardized blanching maneuvers further compromises measurement reliability. To address these challenges, an Optical Fibre Sensor integrated with a Force Sensitive Resistor (FSR) sensor was developed. The system employed an LED, photodetector, and Arduino Uno microcontroller for real-time data acquisition, while MATLAB processed and stored the data in Microsoft Excel. The experiment involved two conditions: one using a pulse sensor and the other utilizing the fibre optic connection, with a consistent group of 10 volunteers. The result demonstrates that the capillary refill time on the subject’s for fibre optic was 0.65±0.14s (mean and standard deviation) compared to pulse sensor which is 1.38±0.46s. These results clearly demonstrate that the fibre optic connection yielded improved measurements for capillary refill time and exhibited greater consistency and precision compared to the pulse sensor. The integration of the Optical Fibre Sensor with FSR sensor enhances CRT measurement reliability, offering potential benefits in assessing tissue perfusion accurately and consistently. These findings contribute to advancing patient care and guiding appropriate treatment interventions based on reliable CRT measurements.